2012
DOI: 10.1111/j.1365-2125.2012.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the oral bioavailability of dabigatran etexilate after co‐medication with rifampicin

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Dabigatran etexilate is an oral prodrug that is rapidly converted to dabigatran, a direct and reversible thrombin inhibitor.• Dabigatran etexilate and dabigatran are not metabolized by the cytochrome P450 system, and dabigatran does not affect the metabolism of other drugs that utilize this system, leading to a low potential for drug-drug interactions.• Dabigatran etexilate, but not dabigatran, is a P-glycoprotein (P-gp) substrate, and the bioavailability of dabigatran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 23 publications
4
78
0
6
Order By: Relevance
“…The prodrug dabigatran etexilate is a substrate for the p-glycoprotein drug efflux transporter encoded by the ABCB1 gene. [23][24][25] The same GWAS from the subset of RE-LY patients found that the ABCB1 rs4148738 polymorphism is associated with an increase in peak plasma concentrations of dabigatran. 22 However, there was no association between dabigatran concentration and adverse events (ie, bleeding, ischemic events), making the clinical consequences of ABCB1 polymorphisms on dabigatran bioavailability uncertain.…”
Section: Pharmacogenetics In Oral Antithrombotic Therapymentioning
confidence: 86%
“…The prodrug dabigatran etexilate is a substrate for the p-glycoprotein drug efflux transporter encoded by the ABCB1 gene. [23][24][25] The same GWAS from the subset of RE-LY patients found that the ABCB1 rs4148738 polymorphism is associated with an increase in peak plasma concentrations of dabigatran. 22 However, there was no association between dabigatran concentration and adverse events (ie, bleeding, ischemic events), making the clinical consequences of ABCB1 polymorphisms on dabigatran bioavailability uncertain.…”
Section: Pharmacogenetics In Oral Antithrombotic Therapymentioning
confidence: 86%
“…The use of TSOACs with other anticoagulants, platelet inhibitors, and nonsteroidal anti-inflammatory drugs increases bleeding risk. All TSOACs interact with the P-gp transporter and interact to varying extents with CYP isoenzyme 3A4 (CYP3A4) [25,[63][64][65][66][67][68]. The greatest CYP3A4 interactions are with apixaban (~25%) [64], followed by rivaroxaban (18%) [69].…”
Section: Concomitant Medications and Tsoacsmentioning
confidence: 99%
“…Показатели снижения плазменных кон-центраций НОАК под влиянием рифампицина получены в исследованиях с участием здоровых добровольцев при его назначении в дозе 600 мг/сут [23][24][25][26]. В ев-ропейской таблице эти показатели приведены дважды.…”
Section: Drug Interactions Of Noac лекарственные взаимодействия ноакunclassified